Frankie Sparks and the Class Pet - Blakemore, Megan Frazer; Sarell, Nadja (New York : Aladdin, 2019)
"Frankie Sparks, the self-proclaimed 'best inventor in the third grade,' does research and creates a tool to try to persuade her classmates that a rat would make the best class pet."--Publisher's description.
Keywords: Schools -- Juvenile fiction; Pets -- Juvenile fiction; Inventions -- Juvenile fiction; Schools -- Fiction; Pets -- Fiction; Inventions -- Fiction